Management of the unstable isolated zygomatic arch fracture: a case study and review of the literature. (12th September 2014) - Veale, B.; Varley, I.; Lee, N.
Abstract Isolated fractures of the zygomatic arch are a relatively common injury, and reduction of the fracture is usually accomplished via a 'closed' or 'indirect' technique such as a temporal approach. Such methods are extremely successful but, on the rare occasion when the reduction is unstable, do not afford access for direct fixation. Several methods of supporting the unstable fragments have been suggested. We compare the methods described and suggest an approach to management of the unstable arch with a case example.